THE PREFERRED MODEL OF ENGLISH FOR PERSONAL, NATIONAL, AND GLOBAL COMMUNICATION IN ELF CONTEXT: A COMPARATIVE STUDY BETWEEN FILIPINOS AND INDIANS - Lasekan, Olusiji (Indonesian Journal of Applied Linguistics, 2018)
An experimental investigation was conducted to compare preferred models of English for personal, national, and global communication in ELF context between Filipinos and Indians. Drawing upon the data gathered through questionnaire and accent recognition survey from over 200 undergraduate students in these two nations, it was revealed that both nationals prefer British English for personal communication. But for national communication, Indians prefer their own standardized variety of English, i.e. Indian English, while the majority of Filipinos chose American English. British English and American English are considered to be the most ideal English varieties to express global identity by Indians and Filipinos, respectively. Finally, the degree of familiarity with the native English varieties which was higher among Filipinos than Indians is inversely proportional to level of awareness of their standard local English variety. Implications of the results and future research directions were also presented.